A Non-Singular Boundary Element Method for Interactions Between Acoustical Field Sources and Structures (Advances in Applied Mathematics and Mechanics, 2023)
Localized point sources (monopoles) in an acoustical domain are implemented to a three dimensional non-singular Helmholtz boundary element methodin the frequency domain. It allows for the straightforward use of higher order surface elements on the boundaries of the problem. It will been shown that the effect ofthe monopole sources ends up on the right hand side of the resulting matrix system.Some carefully selected examples are studied, such as point sources near and withina concentric spherical core-shell scatterer (with theoretical verification), near a curvedfocusing surface and near a multi-scale and multi-domain acoustic lens.